The Impact of MSTN Gene Editing on Meat Quality and Metabolomics: A Comparative Study Among Three Breeds of MSTN-Edited and Non-Edited Cattle - Shan Luo; Yuanqing Liu; Lige Bu; Dezheng Wang; Zhaoyu Wen; Yuqing Yang; Yanan Xu; Di Wu; Guangpeng Li; Lei Yang (Animals)
Myostatin (MSTN) serves as a negative regulatory factor for muscle development. A reduction in MSTN gene expression can enhance muscle mass and increase meat production. However, whether it will impact meat quality traits remains one of the major concerns in the cattle breeding industry. To explore the meat quality traits of MSTN gene-edited cattle, this study compared the meat quality traits of three MSTN gene-edited cattle breeds with those of non-gene-edited cattle, including Luxi, Angus, and Mongolian cattle, and further conducted an analysis in combination with metabolomics. We found that MSTN gene-edited cattle were superior to non-gene-edited cattle in terms of meat pH, shear force, and intramuscular fat content. However, no significant differences were observed in water-holding capacity, water content, and protein content of the meat. Metabolomics analysis revealed three upregulated differential metabolites common to MSTN gene-edited and non-gene-edited cattle across three breeds, namely lactoyl-valine, 3-phenylactic acid, and lactoyl-methionine. Some studies have indicated that these metabolites can improve the meat’s flavor. In this study, we compared the meat quality traits and metabolomics data between MSTN gene-edited and non-gene-edited cattle, and found that the meat quality of MSTN gene-edited cattle was superior to that of non-gene-edited cattle.